Efficacy of double gloving technique in major and minor oral surgical procedures: A prospective study - Padhye, Mukul N. (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: A prospective analysis was carried out over a 1-year period to assess gloves used during 100 major and 100 minor oral surgical procedures to test for efficacy of double gloving in oral surgical procedures. PURPOSE: The purpose of this study was to assess the efficacy of double gloving technique in preventing cross infection in both major and minor oral surgical procedures. MATERIALS AND METHODS: Gloves used during 100 major and 100 minor oral surgical procedures were analyzed to check for glove perforations and skin punctures. 100 sterile gloves were tested as control. STATISTICAL ANALYSIS USED: Chi-square test was used to determine whether there was any difference between the expected and observed values in various categories. RESULTS: A higher number of glove perforations was seen in minor oral surgical procedures compared with major surgeries, dominant hand compared with the nondominant, outer gloves compared with the inner, in procedures which took a longer duration of time to complete, in procedures involving wiring and in the index finger followed by the thumb and the palm. CONCLUSION: Double gloving technique using sterile gloves can be used as an effective means of infection control for all major and minor surgical procedures, especially high-risk procedures involving patients who maybe suffering from or carriers of blood-borne infections.